Mental Health Literacy Among University Students In Semarang City - Diany Ufieta Syafitri (Psychosophia: Journal of Psychology, Religion, and Humanity, 2022)
Increasing mental health problems in Indonesia is not followed by mental health literacy in the community, especially college students. The way people perceive mental health and disorders is closely related to their culture. This study aimed to capture university students' perceptions in the city of Semarang regarding mental health and disorders also attitudes towards psychological help. This study was conducted using qualitative methods, with open-ended questionnaires and focus group discussions. The participants of this study were undergraduate university students aged 21-25 years old recruited through accidental sampling. The data analysis used were coding and categorization. The results showed that 1) the participant includes aspects of spirituality in terms of mental health, 2) the word "stress" is associated with crazy or severe mental disorders, 3) depression is perceived as a continuation of stress or mild anxiety, 4) the participant tends to have a negative attitude to professional psychological help and prefer informal source of help such as family and religious to overcome the problems experienced and emphasizing autonomy in solving problems, and 5) low accessibility to psychological services, insufficient knowledge of psychological services nearby, and tariffs of psychological services were external factors that affect the less favorable attitude towards psychological help.